Comparative proteomics analysis of pomegranate seeds on fruit maturation period (Punica granatum L.) - Shang-yin CAO; Juan NIU; Da CAO; Hao-xian LI; Hui XUE; Li-na CHEN; Fu-hong ZHANG; Di-guang ZHAO (Journal of Integrative Agriculture, 2015)
Seeds play a central role in the life cycle of plants. Seed hardness in pomegranates is of economic relevance, yet scarcely studied and poorly understood in China. In this study, we compared the proteomic differences between Zhongnonghong (soft-seeded) and Sanbai (hard-seeded) pomegranates. A total of 892 protein spots from both varieties were detected on two-dimensional electrophoresis gels (2-DE); 76 spots showed greater than a 1.5-fold or less than a 0.66-fold difference (P<0.05) in Zhongnonghong compared to Sanbai, of which 24 exhibited greater than a 2-fold change. Compared with Sanbai, Zhongnonghong possessed 14 up-regulated, and 10 down-regulated proteins. We identified and annotated 5 of these by using MALDI-TOF-TOF MS: pyruvate dehydrogenase (PDH) E1-β family protein (spot 4 609); alanine aminotransferase 2-like (ALT2L); mitochondrial glycine decarboxylase complex P-protein (spot 5 803); phosphofructokinase B (PfkB)-type family of carbohydrate kinase (spot 8 411); and putative dnaK-type molecular chaperone heat shock cognate protein 70 (Hsc70) (spot 9 006). Of these, 3 proteins (spots 4 609, 5 608, 5 803) were hypothesized to play a role in the formation of seed hardness. The other two proteins (spots 8 411, 9 006) were theorized to play a role in protecting the seeds from adverse stress during periods of fruit maturation. This study sets the foundation for further research on molecular mechanisms related to pomegranate seed hardness.